Analisis Faktor Lingkungan Fisik Rumah yang Mempengaruhi Kejadian Tuberkulosis - Firdaus, Dwiyan Maharani Mutiara; Radi, Radi; Alfiyah, Alfiyah; Rindiana, Elfi (Universitas Hang Tuah Pekanbaru, 2026)
Background: Tuberculosis is a serious health problem in Indonesia. Various factors including home environmental factors can cause tuberculosis. Aim: This study aimed to analyze the influence of home environmental factors (occupancy density, wall type, house ventilation, and floor type) on the incidence of tuberculosis in the Baturraden 1 Health Center Area. Method: This study is an analytical study with a case-control approach that examines the influence of home physical environment variables on the incidence of tuberculosis. The study sample consisted of 48 tuberculosis cases and 48 controls. The research instrument used questionnaires and observation sheets. Data collection will take place in December 2023. The study data were analyzed univariate, bivariate, and multivariate using SPSS 23. Result: The analysis showed that occupancy density influenced tuberculosis incidence in the Baturraden 1 Health Center area (p-value 0.025 OR: 5.549 95%CI: 1.362-22.604). This means that respondents who live in homes with ineligible densities are 5,549 times more likely to suffer from tuberculosis than respondents who live in homes with qualified population densities. Variables that do not affect the incidence of tuberculosis are the type of floor, type of wall, and ventilation of the house. Conclusion: The risk factor for tuberculosis is occupancy density which does not meet health requirements.